Telomere Dynamics in Human Cells Reprogrammed to Pluripotency - Suhr, Steven T.; Chang, Eun Ah; Rodriguez, Ramon M.; Wang, Kai; Ross, Pablo J.; Beyhan, Zeki; Murthy, Shashanka; Cibelli, Jose B. (PloS one, 2009)
Human induced pluripotent stem cells (IPSCs) have enormous potential in the development of cellular models of human disease and represent a potential source of autologous cells and tissues for therapeutic use. A question remains as to the biological age of IPSCs, in particular when isolated from older subjects. Studies of cloned animals indicate that somatic cells reprogrammed to pluripotency variably display telomere elongation, a common indicator of cell "rejuvenation." We examined telomere lengths in human skin fibroblasts isolated from younger and older subjects, fibroblasts converted to IPSCs, and IPSCs redifferentiated through teratoma formation and explant culture. In IPSCs analyzed at passage five (P5), telomeres were significantly elongated in 6/7 lines by >40% and approximated telomere lengths in human embryonic stem cells (hESCs). In cell lines derived from three IPSC-teratoma explants cultured to P5, two displayed telomeres shortened to lengths similar to input fibroblasts while the third line retained elongated telomeres. While these results reveal some heterogeneity in the reprogramming process with respect to telomere length, human somatic cells reprogrammed to pluripotency generally displayed elongated telomeres that suggest that they will not age prematurely when isolated from subjects of essentially any age.